Video-based intervention for children with autism: Towards improved assessment of pre-requisite imitation skills. (26th February 2014) - Rayner, Christopher
Abstract: Objective : To explore the relationship between responses to imitation assessment and video-based intervention (VBI) in children with autism. Methods : Interview- and observation-based imitation assessments were conducted for five boys with autism prior to VBI across three studies. In two of the three studies, the boys' imitative responses to videos with an animated model and a human model were also compared. Results : Participants who were assessed to have strong imitation skills were also those who responded more positively to VBI. No clear differences were reported in the boys' responses to the equivalent videos with the animated model and the human model. Conclusions : The level of imitation skills required for successful VBI is relative to the target behaviour. Revision of existing imitation assessment measures, as well as development and validation of more comprehensive measures is warranted for use in conjunction with VBI.